(185) تحليل خصائص ومتغيرات السوق المصري : (الجزء الثالث) الإطار التطبيقي: سوق الأدوية-سوق السلع الغذائية والزراعية-سوق حديد التسليح والأسمنت Analysis of the characteristics and variables of the Egyptian market: Part Three: The applied framework: The pharmaceutical market - The food and agricultural commodities market - The reinforcing steel and cement market - محرم الحداد; حسام مندور; فادية عبد السلام; خالد عبدالوهاب; محمود عبدالحي واخرون (معهد التخطيط القومي،, 2018)
2005